Are sensational interests examples of everyday sadism, or a general indicator of antagonism? - Weatherill, Charlotte Lauren (2019)
The present study used an online survey of self-report questionnaires to examine general personality traits (assessed using the HEXACO Personality Inventory- Revised) and the Dark Tetrad (narcissism, Machiavellianism, psychopathy, and sadism) in relation to sensational interests, looking specifically at the violent occult and militarism subscales. It was hypothesised that both subscales of sensational interests would be predicted by low honesty-humility, low emotionality, low agreeableness, low conscientiousness, high extraversion and high openness scores (Egan et al., 1999; Paulhus & Williams, 2002), as well as high scores on all of the Dark Tetrad measures (Jones & Paulhus, 2011) with low honesty-humility and sadism being the biggest predictors of both subscales. There were 242 participants (60.7% female, 36.8% male, 2.5% identifying as ‘other’; mean age 27.05 years (SD=9.32)). Results showed how the Dark Tetrad dimensions are correlated with the six HEXACO dimensions and how all of these traits are correlated with the sensational interest subscales. It was revealed that the violent occult subscale of sensational interests could be predicted by low agreeableness, high openness, high psychopathy, and high sadism whilst militarism could be predicted by low emotionality and high sadism. High sadism scores were found to show the largest correlation with both the violent occult and militarism scores. Implications of the study and recommendations for future directions are discussed.